Regular clocking-based Automated Cell Placement technique in QCA targeting sequential circuit. (March 2022) - Bhowmik, Dhrubajyoti; Pramanik, Amit Kumar; Pal, Jayanta; Sen, Pinaki; Singh, Ayush Ranjan; Saha, Apu Kumar; Sen, Bibhash
Abstract: Quantum-dot cellular automata (QCA) is field-coupled nanotechnology that achieves high device density, high switching speed, and low power dissipation. The flow of information within QCA is fully controlled by the position of the electrons only. A proper cell placement and its respective clock zone for the correct logic operation become the utmost design requirement. Insufficient research in this direction and appropriate use of regular clocking requires rigorous research in this area. An appropriate routing channel to adopt a stable and steady underlying clock scheme plays an essential role in positioning QCA cells. This paper presents a systematic placement of QCA cells targeting sequential logic, which makes efficient use of the underlying regular clocking scheme. The proposed method is verified by implementing the SR and D flip flop incorporating the USE clocking scheme. The effectiveness of the proposed cell positioning algorithm is reported. A significant performance improvement is observed, which advocates the importance of such a scheme in QCA circuit design. Graphical abstract: